Neuropeptides in the desert ant Cataglyphis fortis: Mass spectrometric analysis, localization, and age‐related changes. Issue 4 (27th September 2016) - Schmitt, Franziska; Vanselow, Jens T.; Schlosser, Andreas; Wegener, Christian; Rössler, Wolfgang
ABSTRACT: Cataglyphis desert ants exhibit an age‐related polyethism, with ants performing tasks in the dark nest for the first ∼4 weeks of their adult life before they switch to visually based long‐distance navigation to forage. Although behavioral and sensory aspects of this transition have been studied, the internal factors triggering the behavioral changes are largely unknown. We suggest the neuropeptide families allatostatin A (AstA), allatotropin (AT), short neuropeptide F (sNPF), and tachykinin (TK) as potential candidates. Based on a neuropeptidomic analysis in Camponotus floridanus, nano‐LC‐ESI MS/MS was used to identify these neuropeptides biochemically in Cataglyphis fortis . Furthermore, we show that all identified peptide families are present in the central brain and ventral ganglia of C. fortis whereas in the retrocerebral complex only sNPF could be detected. Immunofluorescence staining against AstA, AT, and TK in the brain revealed arborizations of AstA‐ and TK‐positive neurons in primary sensory processing centers and higher order integration centers, whereas AT immunoreactivity was restricted to the central complex, the antennal mechanosensory and motor center, and the protocerebrum. For artificially dark‐kept ants, we found that TK distribution changed markedly in the central complex from days 1 and 7 to day 14 after eclosion. Based on functional studies in Drosophila, this age‐related variation of TK is suggestive of a modulatory role in locomotion behavior in C. fortis . We conclude that the general distribution and age‐related changes in neuropeptides indicate a modulatory role in sensory input regions and higher order processing centers in the desert ant brain. J. Comp. Neurol. 525:901–918, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Neuropeptides are known to regulate animal physiology and behavior. The present study uses mass spectrometry and immunohistology to analyze the neuropeptide families allatostatin A, allatotropin, short neuropeptide F, and tachykinin, which we deem regulatory for behavioral transitions in the desert ant Cataglyphis fortis .